2020
DOI: 10.1302/2633-1462.111.bjo-2020-0141.r1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on morbidity and mortality in neck of femur fracture patients

Abstract: Aims Within the UK, around 70,000 patients suffer neck of femur (NOF) fractures annually. Patients presenting with this injury are often frail, leading to increased morbidity and a 30-day mortality rate of 6.1%. COVID-19 infection has a broad spectrum of clinical presentations with the elderly, and those with pre-existing comorbidities are at a higher risk of severe respiratory compromise and death. Further increased risk has been observed in the postoperative period. The aim of this study was to assess the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 18 publications
(16 reference statements)
0
44
0
Order By: Relevance
“…Comparative meta-analysis was performed from 14 studies [ 1 , 8 , 15 , 16 , 19 – 28 ] for 30 days mortality, from 4 studies [ 8 , 16 , 17 , 22 ] for in-hospital mortality, and 6 each for the length of hospital stay [ 1 , 8 , 15 , 17 , 25 , 28 ] and number of complications. [ 1 , 8 , 14 , 18 , 22 , 26 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative meta-analysis was performed from 14 studies [ 1 , 8 , 15 , 16 , 19 – 28 ] for 30 days mortality, from 4 studies [ 8 , 16 , 17 , 22 ] for in-hospital mortality, and 6 each for the length of hospital stay [ 1 , 8 , 15 , 17 , 25 , 28 ] and number of complications. [ 1 , 8 , 14 , 18 , 22 , 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of patients was 81.79 years with a range from 71.9 to 86.5 years. The review included 925 males and 2028 females reported in 18 studies [ 1 , 7 , 8 , 12 15 , 17 26 , 28 ] and the mean length of hospital stay ranged from 5 ± 2.6 to 24.21 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an increased mortality rate among patients with hip fractures who were diagnosed with COVID-19 [3,11,16,24,[27][28][29][30][31]. In this study none of the con rmed or suspected COVID-19 patients died in-hospital so the COVID-19 diagnosis may not be driving this increased risk for mortality.…”
Section: Discussionmentioning
confidence: 59%
“… 30 Given the pathophysiology of COVID-19 as a viral respiratory illness, the percentage of patients experiencing pneumonia during the pandemic was higher as compared to pre-pandemic years. 31 The higher rates of AKI and pneumonia for COVID-positive hip and distal femur fracture patients, resulting in higher rates of mortality, is also supported by a study by Ward et al 32 who demonstrated similar findings. Our results therefore demonstrate the importance of early recognition and management for AKI and pneumonia, especially for COVID-positive patients.…”
Section: Discussionmentioning
confidence: 70%